Fosfomycin concentrations in epithelial lining fluid in weaning piglets - Soraci, Alejandro Luis (2012)
Concentrations of fosfomycin into the epithelial lining fluid (ELF) were studied by bronchoalveolar lavage (BAL) on 6 healthy weaning piglets after the administration of disodium fosfomycin 15 mg/kg intramuscularly (IM). The mean concentrations of fosfomycin in ELF were lower than those in plasma at all sampling time points. Fosfomycin concentrations in ELF were 12.1 % of those in serum. The degree of penetration of fosfomycin into the ELF was determined by comparing the AUC0–8 in ELF with the AUC0–8 in serum. The ratio AUCELF / AUCserum was 0.15 ± 0.02. The Cmax in serum and in ELF were 45.00 ± 2.51 and 3.10 ± 0.95 µg/ml, respectively. These concentrations were achieved at different times (Tmax in serum and ELF: 1.00 ± 0.00 and 2.58 ± 0.49 h, respectively). Effective bacterial killing can be expected from the first antibiotic dosage when the pathogen’s MIC is covered for at least 60–70% of the dosing interval. Different authors have determined a fosfomycin MIC90 for Streptococcus sp (important respiratory pathogens in piglets) of 0.25 µg/ml. Fosfomycin concentrations in ELF remained above the MIC90 value for Streptococcus during more than 8 h post IM administration of 15 mg/kg in weaning piglets. However, additional studies should be carried out in the lungs of infected pigs.